Khul’i (Right of Redemption) under Sharia Courts Rules of Bauchi State, Nigeria, 2013: Issues and Challenges - Ibrahim Danjuma; Umar Sulaiman Abbo Jimeta (Faculty of Law, Hasanuddin University, 2018)
In the year 2000, most of the States in Northern Nigeria re-introduced Sharia as part of their legal system in disposing of both civil and criminal cases. Bauchi State was among the States that re-introduced Sharia as part of its legal system. Based on that, Sharia Courts were created to replace Area Courts, and Sharia Courts Civil Procedure Rules was enacted to regulate the proceedings before the said Sharia Courts on Civil Matters. The Bauchi State Sharia Courts Civil Procedure Rules, 2001 did not contain a provision on Khul’i. Prior to the amendment of Bauchi State Sharia Courts Civil Procedure Rules, Judges of Sharia Courts were in a serious dilemma as to the amount of money to be paid by a woman in order to relieve herself from the bond of marriage. This is because Khul’i is a right accorded to a wife to remove herself from the union of marriage (to get a divorce) by compensating her husband. In order to address the above problem and others, Sharia Courts Civil Procedure Rules of Bauchi State, 2001 was amended in 2013 and right of Khul’i (Redemption) was incorporated under Order 21 of the Bauchi State Civil Procedure Rules, 2013. With the amendment of the said Sharia Courts Civil Procedure Rules of Bauchi State, instead of addressing the problem of a quantum formula for Khul’i, rather brought a controversy to the said issue. Therefore, this study critically examines the Qur’anic Verses, Hadith and the opinion of the Islamic Scholars on Khul’i and compare them with Order 21 Right of Redemption (Khul’i) of Sharia Courts Civil Procedure (Amendment) Rules of Bauchi State, 2013 so as to ascertain its consistency or otherwise.